COMPUTER BOOKS. (Bookseller, 2003)
The article presents information on various computer books. Probably the most important title in a range of books from McGraw-Hill, 'Office 2003: The Complete Reference' covers the latest Office suite from Microsoft Corp., which has an estimated 12 million users. 'How To Do Everything with Office 2003,' by Laurie Ulrich is a more gentle introduction to the Windows environment for beginners, this is still a comprehensive guide to the software used in 90% of the world's offices. 'You Can Do It!,' by Francis Glassborow bridges the gap between computer users and programmers. Written by a successful coder and writer on C++, it explains what programs are and how they are made, but gets the reader involved from chapter one with hands-on programming. The CD contains all the support needed to start programming on a Windows PC. INSET: The best of the rest.